2003
DOI: 10.2337/diacare.26.5.1507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urinary 8-Hydroxydeoxy-Guanosine as a Novel Biomarker of Macrovascular Complications in Type 2 Diabetes

Abstract: OBJECTIVE -To evaluate urinary 8-hydroxydeoxyguanosine (8-OHdG) as a marker for the progression of diabetic macroangiopathic complications. RESEARCH DESIGN AND METHODS -The content of urinary 8-OHdG, common carotid intima-media thickness (IMT), the coronary heart disease (CHD) risk score, the severity of diabetic retinopathy, and urinary albumin excretion were examined in 96 patients with type 2 diabetes, including 32 patients who had been nominated for the Kumamoto Study [Shichiri M, et al. Diabetes Care 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 26 publications
8
119
3
Order By: Relevance
“…When such damaged DNA is repaired, 8-OHdG is produced and excreted unchanged in the urine. 15 Previous studies 16 in experimental diabetes demonstrated decreased renal NO levels as a consequence of increased oxidative stress, primarily as a result of enhanced expression of superoxide dismutase and catalase. In those studies, NOS expression was not studied.…”
Section: Discussionmentioning
confidence: 98%
“…When such damaged DNA is repaired, 8-OHdG is produced and excreted unchanged in the urine. 15 Previous studies 16 in experimental diabetes demonstrated decreased renal NO levels as a consequence of increased oxidative stress, primarily as a result of enhanced expression of superoxide dismutase and catalase. In those studies, NOS expression was not studied.…”
Section: Discussionmentioning
confidence: 98%
“…8-OHdG is an accepted indicator of oxidative DNA damage, and its levels in serum and urine have been widely measured to monitor the degree of oxidative stress. 14,15 Plasma/serum NT levels have been used as a marker of oxidative and nitrosative stress and as a specific indicator of systemic peroxynitrite formation. 16,17 It should be noted that in the present study the levels of serum and urinary 8-OHdG and serum NT were higher in the diabetic patients with microalbuminuria than in those with normoalbuminuria, despite comparable levels of hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…From these clinical trials, it is possible that a pancreatic effect of GKAs could not be expected when pancreatic beta cells have been impaired. It is well known that the level of 8-hydroxydeoxyguanosine, a marker of oxidative stress, is increased in diabetic patients and independently associated with mean HbA 1c [31]; in addition, increased oxidative stress influences beta cell function, and antioxidant treatment can exert beneficial effects in diabetes, with a preservation of beta cell function [32]. We therefore investigated the effect of oxidative stress on GKA-induced changes in the expression of genes involved in beta cell function and proliferation.…”
Section: P22 Phox Expression (Au)mentioning
confidence: 99%